Penggunaan Bahasa Pemrograman Python dalam Menganalisis Hubungan Kualitas Kopi dengan Lokasi Pertanian Kopi - Regina Lo; Alfred Edbert Yunanto; Rasya Nuhaifa Movia; Lambert Aditama Soehardjianto; Ferdinand Wangsa; Natalie Asdyo Lidjaja; Rahmi Yulia Ningsih (Lembaga Pengembangan Kinerja Dosen, 2023)
Coffee is a drink that everyone loves, however, not all coffee consumed has good quality. The quality of coffee is influenced by various factors, one of which is the location of the farm. Therefore, it is very important to analyze the relationship between coffee quality and relevant farm sites. To achieve this goal, the author conducted a study that aims to explore the relationship between the quality of coffee and the elevation location where coffee is grown. The author collects data through a website called kaggle. The author analyzes data with the exploratory data analysis (EDA) method using the Python programming language to analyze data between the quality and area of coffee farming in a country that produces a lot of coffee. Through this study, the Author found that the higher the coffee farming location, the better the quality of the coffee produced.